Interventional Radiology in Management of Pancreatic Trauma - Dai, Rui; Avery, Laura; Arellano, Ronald S. (Digestive Disease Interventions, 2025)
Pancreatic traumatic injuries are uncommon but can have devastating clinical consequences and prognosis is often associated with high morbidity and mortality. Interventional radiology plays an important role in both early and late clinical presentations of pancreatic trauma to decrease the rates of morbidity and mortality, major complications, and improve clinical outcomes. This article will describe image-guided techniques to diagnose and manage pancreatic trauma and associated complications.
Keywords: pancreas; pancreatic duct; trauma; computed tomography